A possibility of the short-term strong earthquakes forecasting on materials of cloudiness anomalies satellite surveys - Vorobiov, Anatolii; Golubov, Stanislav (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2018)
For a prediction of sharp growth of seismicity level and preservation of many people life the most important the short-term forecast of strong earthquakes (ZTR) is the appearance of cloudiness anomalies before strong earthquakes. Today the science has certain achievements in this area. One of criteria of the short-term forecasting is emergence of cloudiness anomalies before strong earthquakes. Results of identification by means of satellite surveys of linear anomalies of cloudiness which were observed before strong earthquakes in Asia Minor are given in work. The archival images registered by a sensor of MODIS which is established on the meteorological AQUA and TERRA satellites were used. The task consisted in that at the known time and the place of a strong earthquake, to carry out the analysis of cloudiness in the satellite images registered in previous days for the purpose of detection of cloudiness anomalies (in particular linear) to define time difference between emergence of anomalies of cloudiness and a strong earthquake. It turned out that this time difference is obviously connected with a geological structure of the region. For example, cloudiness anomalies near the city of Anapa (Russia) were observed before a strong earthquake (on November 9, 2002, the magnitude of 4.4 points) in 2 days, and cloudiness anomalies before an earthquake on October 23, 2011, magnitude 7.2 near the lake Van (Turkey) began to be observed in 10 days before earthquake, and the most accurate and extended linear cloudiness anomaly was observed in 5 days prior to this earthquake.